Analisis Keterlambatan Penyelesaian Port Disbursement dalam Kinerja Operasional pada Perusahaan Jasa Keagenan Kapal - Rosalia Indah Sari; Bugi Nugraha; Prima Yudha Yudianto; Intan Sianturi (Pusat Riset dan Inovasi Nasional, 2024)
Delays in the completion of Port Disbursements in ship agency companies can interfere with operational performance in ship agency companies where this delay factor arises from internal and external parties. This article explains that there are still obstacles/factors that cause the process of completing a ship's Port Disbursement has not run on time due to obstacles between shipping agents, related agencies, and Port Business Entities, This research uses qualitative research with data collection and interviews, while the data collection in this study is by data reduction, and the existence of primary and secondary data sources. Based on the results of the research obtained by the researcher, the cause of the delay in completing Port Disbursement uses 4 (four) elements in the Fishbone Diagram, namely Man, Material, Method, and Machine. These factors cause operational performance in completing Port Disbursement on time which ultimately causes queues/piles of settlement files, so that this will have an impact on the company's cash flow to be unsmooth. The solution provided by the company is to continue to evaluate and improve what makes the obstacle factors experienced by the operational and financial divisions in completing the settlement.